Effect of heat-treatment processing on microstructure and properties of 40Cr3Mn3Ni3Si2Mo ultra-high strength steel - SUN You; CHEN Xiong; HU Jiafeng; ZHAO Zhuo; WANG Lijun; LIU Chunming (Cailiao gongcheng)
A medium carbon alloy steel 40Cr3Mn3Ni3Si2Mo is designed and prepared， and tempering is carried out after hot rolling， hot rolling plus refrigerating treatment， as well as quenching plus refrigerating treatment respectively. Microstructural characterization and properties testing are conducted on the heat-treated samples to investigate microstructural evolution. The relationship between processing， microstructures and mechanical properties is established， and the mechanism of strengthening and toughening is illuminated. Consequently， the principles for composition design and process optimization of quenching and partitioning （Q&P） typed ultra-high strength steels with high strength and plasticity are figured out. The results show that multiphase microstructures of tempered martensite and carbon-enriched austenite are achieved through tempering on the hot-rolled testing steel， while its strength fails to reach the level of ultra-high strength steels due to high volume fraction of retained austenite. The match of strength and ductility of the hot-rolled testing steel increases significantly through low temperature tempering after refrigerating treatment because of the improved phase proportion and distribution. When the testing steel is refrigerating treated and tempered instantly after oil quenching to weaken the effect of austenite stabilization， more excellent comprehensive properties are achieved with 1506 MPa in yield strength， 1895 MPa in ultimate tensile strength and 16.7% in elongation. Moreover， a feasible approach to increase the strength and plasticity of 1800-1900 MPa graded ultra-high strength steels is proposed： through controlling the martensitic phase transformation kinetics by alloying design and process optimization， austenite of about 20% in volume fraction is retained within martensite after incomplete quenching， its stability is reinforced by tempering assistant partitioning. Thus， the elongation increases to 15%-18%， with the yield strength lowered slightly to 1400-1600 MPa.